Oral delivery of bovine tuberculosis vaccine to free-ranging white-tailed deer - VerCauteren, Kurt; Feuka, Abigail; Lavelle, Michael; Glow, Michael; Kohen, Keely; Ryan, Patrick; Aderman, Tony; Duffiney, Anthony; Palmer, Mitchell; Boggiatto, Paola M.; Kanipe, Carly; Hamby, Hayden; et al. (Frontiers in Veterinary Science, 2025)
IntroductionFree-ranging white-tailed deer (Odocoileus virginianus) are a self-sustaining reservoir for bovine tuberculosis (bTB) in northeastern lower Michigan, (United States) continually putting the area’s cattle industry at risk. Liberal recreational deer harvest, baiting bans, and mitigation measures on farms have reduced but not eliminated bTB in deer nor have they eliminated transmission to cattle. With apparent prevalence in deer being low (1–2%) but constant, vaccination could be an additional tool to aid in addressing the problem and merits investigation. Mycobacterium tuberculosis Bacillus Calmette-Guérin (BCG) vaccine is a widely used human vaccine for tuberculosis that has also been well studied in domestic livestock and wildlife. It is the primary vaccine candidate, and oral delivery is the logical means for delivering it to free-ranging deer, although this has never previously been attempted.Materials and methodsBuilding off methods and strategies developed for vaccinating deer, we incorporated BCG vaccine into vaccine delivery units (DUs), consisting of a food-based matrix. We deployed DUs at sites in Michigan with a historically high prevalence of bTB. At each site, 100 DUs were placed systematically 2.5-m apart on 50-m x 10-m grids and monitored with still and video cameras. Consumption, still images, and video data were analyzed to assess uptake of vaccine DUs by deer.Results and discussionVaccine DUs were deployed in 2024 at 11 agricultural sites on private land which had previously demonstrated moderate to high deer activity and at all but two sites >50% of distributed vaccine DU’s were consumed, with 100% consumed at two sites. Deer learned to seek out and consume vaccine DU’s in just 1 to 3 days, with individuals often eating more than the 1 or 2 needed to vaccinate themselves. This high level of consumption was in spite of an exceptionally warm and dry winter, where deer were less food stressed than usual.